Effects of spatial bottom friction parameterization scheme on the tidal dynamics in the macrotidal East China Seas - Qian, Suhui; Du, Yunfei; Wei, Zilu; Zhang, Jicai; Cheng, Jun; Wang, Daosheng; Wang, Ya Ping (Frontiers in Marine Science, 2023)
In this study, the effects of different bottom friction coefficient (BFC) parameterization schemes on the modelling of four principal tidal constituents (M2, S2, K1, O1 tides) in the macrotidal East China Seas were investigated by using a high-resolution model based on FVCOM (Finite Volume Community Ocean Model). The applied BFC schemes include: the empirical constant (EC-BFC), sediment-dependent form (SD-BFC), and spatial varying BFC obtained from adjoint data assimilation (SV-BFC). The comparisons between the simulated results and the observations from satellite altimeters and tidal gauge stations indicated that the SV-BFC scheme is superior to others. The locations of amphidromic points calculated with EC-BFC and SD-BFC were in the northwest of those from SV-BFC. The variations in tidal dynamics between different BFC schemes were closely related to the spatial distributions of BFCs, especially in high-valued BFC areas, e.g., the West Korea Bay, the South Yellow Sea, and the eastern coasts of Jiangsu, Zhejiang and Fujian provinces. The tidal energy flux transporting into Bohai and Yellow Seas increased under the SV-BFC scheme, while smaller tidal energy flux transporting from the Korea Strait was generated by SV-BFC as compared to those from EC-BFC and SD-BFC. The high-valued BFC areas in the SV-BFC scheme dissipated larger amounts of tidal energy, and the average values of Simpson-Hunter numbers were lower than those with the other two schemes. However, the values of Simpson-Hunter numbers increased in the West Korea Bay and Jianghua Bay with high-valued BFCs because of the decreasing current velocity under the headland-shaped topography.